Evaluation of the impact of residual anhydramnios following preterm premature rupture of membranes on respiratory distress syndrome - Şahin, Erdem; Madendağ, Yusuf (Perinatal Medicine Foundation, 2021)
Objective The aim of the present study was to evaluate the impact of residual anhydramnios following preterm premature rupture of membranes (PPROM) on respiratory distress syndrome (RDS) after the pregnancy was expectantly managed. Methods This study was retrospectively conducted at Erciyes University Medical School, Turkey. It assessed women with singleton pregnancies admitted to the hospital between 2010 and 2020 for expectant management of PPROM between 24th and 28th gestational weeks. The patients were divided into three groups as follows: (1) anhydramnios, (2) oligohydramnios, (3) normal amniotic fluid volume (AFV). Main outcome measure was as follows: The first evaluation was AFV at admission and the primary outcome was a neonatal RDS. Adjusted odds ratios (aOR) and 95% confidence interval (CI) for RDS were calculated for each AFV-at-presentation adjusting for gestational age (GA) at PPROM, GA at delivery, latency period, birth-weight percentile, cesarean birth, and chorioamnionitis. Results Of the 440 women with PPROM, 261 fulfilled the inclusion criteria. There were 125 (47.8%) with normal AFV, 71 (27.3%) with oligohydramnios, and 65 (24.9%) with anhydramnios at admission. The maternal demographic characteristics were similar among the groups. Birth weight was significantly different among the groups. RDS was highest in the anhydramnios group (64.6%). Decreased AFV was not associated with RDS in either oligohydramnios or anhydramnios at presentation. A GA at PPROM, latency period >30 days, and cesarean delivery were co-factors in the outcome. Conclusion Our results indicated that oligohydramnios and anhydramnios were not associated with RDS risk, but GA at PPROM and delivery, latency period, and cesarean delivery were independently associated with the RDS risk.